DNA barcoding and High-Performance Liquid Chromatography as golden standards of authentication in Blumea balsamifera and Ehretia microphylla products - ALYSSA MARIE A. LOLA; SAM DOMINIC A. BINAG; NIÑA KATHRYN G. ALFECHE; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Lola AMA, Binag SDA, Alfeche NKG, Alejandro GJD. 2025. DNA barcoding and High-Performance Liquid Chromatography as golden standards of authentication in Blumea balsamifera and Ehretia microphylla products. Biodiversitas 26: 1258-1270. In the Philippines, the Department of Health (DOH) has included Blumea balsamifera (sambong) and Ehretia microphylla (tsaang-gubat) among the top ten medicinal plants in the country. Sambong is known for treating urinary stones, while tsaang-gubat is used for helping increase the motility of intestines. Despite their known healing effects, there remains a lack of strict implementation for the approval of these products to be commercially available. This study aimed to employ DNA barcoding and High-Performance Liquid Chromatography (HPLC) by creating a Standard Reference Material (SRM) for both methods. Eight blindly selected sambong herbal medicinal products (HMPs), and six blindly selected tsaang-gubat HMPs are authenticated using the stated methods. DNA barcoding reveals that samples BB4 and EMP1 are cases of substitution for the products containing Oryza glaberrima and Cymbopogon citratus, respectively. HPLC analysis also reveals that all sambong derived HMPs contain quercetin, except for samples BB2, BB4, and BMP3, whereas for the tsaang-gubat herbal products, only sample EMP1 does not contain rosmarinic acid as its active compound. Dissidence in the results indicates that both protocols should be used in coordination as standard authentication tools to promote accuracy of the results and to provide safety to all the consumers. Furthermore, DNA barcoding authenticates the actual plant material used while HPLC checks the presence of active compounds.